Pancasila-driven Character Education as a Foundation towards Multicultural Society A Case Study at Bruder Singkawang Elementary School - Era Tazkiyah; Sugeng Utaya; Sumarmi (Didaktika: Jurnal Kependidikan, 2024)
Character education is an important part of the world of education. Teachers are required to be able to have character and provide character education in accordance with Pancasila. The aim of this research is to analyze and describe various successful forms of character education carried out by teachers at the Pancasila-based Bruder Singkawang Elementary School which helps strengthen the multicultural society of Singkawang City and have an awareness of differences. Data collection techniques use interviews, observation and documentation. Data analysis techniques use Miles and Hubberman in the form of data reduction, data presentation, and conclusions/verification. The results of the research show that teachers at Bruder Singkawang Elementary School can implement various real character education actions into learning such as forming peer tutors, saying greetings according to each religion, strengthening understanding of differences from stories of life experiences, and other real actions as well as other activities in the environment. schools such as the language month program, GSM and GKM. The activities carried out in learning are carried out differently between teachers depending on creativity to develop character education. The understanding of differences from the teachers at Bruder Singkawang Elementary School helps students to gain experience regarding the value of differences and remains based on Pancasila, thereby helping to strengthen character in a multicultural society, especially in Singkawang City.